Comparative study of strength-based damage evolution in ultra-high-performance concrete (UHPC) and conventional concrete (CC) under dynamic loading. (September 2021) - Sun, Qiran; Williams, Brett; Loeffler, Colin; Martin, Bradley; Heard, William; Frew, Danny; Nie, Xu
Highlights: Well-controlled intermittent dynamic loading experiments are conducted to introduce various degrees of damage in the concrete specimens through the use of a modified Kolsky bar apparatus with pulse shaping techniques. Quantitative relationships between strength-based damage parameter D and plastic strain ε p are obtained. Experimental results indicate that damage initiates prior to the peak stress, and there is a distinct difference in damage evolution between different concrete materials. Our investigation demonstrates a more comprehensive view of damage evolution in concrete materials. Abstract: The initiation and development of damage inside cementitious materials subjected to dynamic loadings, which is manifested by the cracking and fragmentation process, have a significant contribution to the load-bearing capacity of these materials. However, current popular concrete models hypothesize that damage only initiates after the specimen reaches its peak stress, and due in part to the lack of validation from sufficient experimental data, none of the models entertain the possibility of variation in damage evolution among different types of concretes. In this study, the evolution of damage in an ultra-high-performance concrete (UHPC) and a conventional concrete (CC), characterized by the degree of strength degradation, are comparatively investigated throughout the entire pre-/post-peak deformation process as a function of carefully measured plastic strain. Well-controlled intermittent dynamic loadings are achieved on a modified Kolsky compression bar apparatus to first introduce various degrees of damage in the concrete specimens, and then the carefully preserved specimens are tested for residual strength. Coupling with pulse shaping techniques, the incident wave profiles are tailored for UHPC and CC specimens to acquire dynamic stress equilibrium and constant strain-rate deformation. Further evaluation on the residual strength of damaged specimens reveals that damage initiates prior to the peak stress, and there is a distinct difference in damage evolution between these two types of concrete materials. This investigation demonstrates a more comprehensive view of damage evolution in concrete materials and offers novel experimental data to assist the damage model development. Graphical abstract: Image, graphical abstract